Influence of Self-Efficacy as a Mediator on Time Management and Students’ Performance Relationship in Malaysian Online Distance Learning Institutions - Zahir Osman,; Wardah Mohamad,; Ratna Khuzaimah Mohamad,; Liana Mohamad,; Tuan Fatma Tuan Sulaiman, (2018)
Academic achievement is the main objective amongst students in tertiary education institutions. A tertiary education institution’s performance normally will be measured by its ability to retain its students and the students’ resultsStudents’ failure rate too high will give the higher education institution a negative image Not many have conducted studies on online distance learning students’ performance.